An automatic identification algorithm of internal solitary wave for mooring data based on geometric characteristics of the flow field - Rong, Lintai; Xiong, Xuejun; Chen, Liang (Frontiers in Marine Science, 2023)
Internal solitary wave (ISW) is one of the most important sub-mesoscale phenomenas in the ocean, and detection of which is of utmost significance for marine exploitation, ecological environment protection and military affairs. Therefore, in this study, an automatic algorithm for the identification of ISWs was proposed based on the geometric characteristics of the flow field. The algorithm was applied to calculate the characteristic parameters of the ISWs and its reliability was further verified, indicating that the algorithm can effectively detect the ISWs and provide a reference for preventing and avoiding ISWs in ocean engineering.